Effects of Using Technology on the Academic Performance in Mathematics of the College Millennial Learners - Chona S. Rizada; Raymond P. Rey (East Asian Journal of Multidisciplinary Research, 2023)
The educational landscape has changed significantly with technology. It affects how people live, work, play, and learn, wherein technology has challenged how education is managed and the methods and strategies in teaching, particularly in mathematics. This research is experimental and employed the multi-group pretest–posttest design to assess the effects of using technology on college millennial students’ academic performance in mathematics. The control group was subjected to the lecture-discussion method without using technology, while another section served as the experimental group and was exposed to technology-based instructions. The questionnaire was used to gather data from the respondents to determine the extent level of the effect of technology on student’s academic performance in mathematics. The results of the post-test increased significantly, and the experimental group results increased is 2.58 percent higher than controlled group. Teaching using technologies enhanced the student’s academic performance in mathematics, and it was concluded that teaching with the aid of technology is better than lecture type or traditional teaching methods.